Determine The Effect of The Leadership Style of The Head of The Room On The Performance of Nurses in The Inpatient Roomof The Rokan Hulu Regional General Hospital in 2020 - Ismail Marzuki Hasibuan; Nopriadi; Lita; Jasrida Yunita; Siska Mayang Sari (Journal of Midwifery and Nursing, 2021)
The leadership style of the head of the room plays a very important role in improving nursing performance.  Based on the results of interviews with 10 nurses in the inpatient room of RSUD Rokan Hulu, it was found that nurses could not improve their performance because there was still a lack of direction from the head of the room when there was a problem in the room and the room head's ability to provide future goals was still low.  This study aims to determine the effect of the leadership style of the head of the room on the performance of nurses in the inpatient room of the Rokan Hulu Regional General Hospital.  This research is quantitative analytic observational with a cross-sectional design.  The study was conducted from August to September 2020. A sample of 82 respondents was taken using a proportional sampling technique.  Data generated by univariate, bivariate, multivariate analysis with multiple logistic regression risk factor models.  The results showed that the performance of nurses was good 52.4%, good leadership style was 63.4%.  There is an influence of leadership style on nurse performance (p 0.004).  A good leadership style has the opportunity to improve the performance of nurses to be good 3,673 times after being controlled by tenure.  The conclusion is that there is an effect of leadership style on nurse performance after being controlled by tenure.  It is recommended for the hospital to provide training and provide leadership seminars to the head of the room so that the head of the room can lead and direct the nurse to work better, evaluate the leadership of the head of the room, implement a reward and punishment system.